An unusual presentation of a rare benign tumor in the head and neck: A review of hibernomas. (13th January 2015) - Trujillo, Oscar; Cui, Isabelle H.; Malone, Melanie; Suurna, Maria
<x xml:space="preserve">Abstract</x> Hibernomas are rare benign tumors that may present in the head and neck in an unusual manner similar to more common malignant tumors such as lymphoma. Our case report describes several characteristics of a patient and benign tumor presentation that is atypical for the usual presentation of hibernomas as reviewed in the literature. Although hibernomas are rare, our report and review of the literature highlights a particular patient population and important key findings that should make one consider these benign tumors in the differential diagnosis of a young patient presenting with a neck mass. Laryngoscope, 125:1656–1659, 2015